Mediation Effect of Self-Efficacy and Resilience on the Psychological Well-Being of Lebanese People During the Crises of the COVID-19 Pandemic and the Beirut Explosion - Hong, Jihoon; Mreydem, Hussein Walid; Abou Ali, Bayan Tarek; Saleh, Nada Omar; Hammoudi, Sajida Fawaz; Lee, Jukab; Ahn, Junseok; Park, Jangho; Hong, Youjin; Suh, Sooyeon; Chung, Seockhoon (Frontiers in Psychiatry, 2022)
Introduction Self-efficacy signifies an individual's belief in their own ability to perform the actions required to achieve a particular performance. In this study, we used an online survey to assess the mediation effect of resilience and self-efficacy on the overall psychological well-being of Lebanese people during the crises of the COVID-19 pandemic and the Beirut explosion. Methods Overall, 567 Lebanese people participated in an online survey between March 17‒28, 2021. The survey included the Stress and Anxiety to Viral Epidemics-9 items (SAVE-6), Patient Health Questionnaire-9 (PHQ-9), Connor‒Davidson Resilience Scale-2 items, WHO-5 Well-being Index, General Self-Efficacy scale, and a single item on insomnia. We also assessed their risk perception regarding exposure to COVID-19 or explosions. Results About 53% of participants were assessed as having depression (PHQ-9 ≥ 10) in the recent crisis. About half of participants (52·3%) reported feeling more stressed by COVID-19 than by the Beirut explosion, and 23·4% felt more stressed by the Beirut explosion than by COVID-19. Only the SAVE-6 score differed significantly between groups with greater stress responses to COVID-19 and the Beirut explosion. Self-efficacy mediated the influence of depression on people’s psychological well-being, and self-efficacy and resilience mediated the influence of viral anxiety on but affected the impact of anxiety about the viral epidemic on their psychological well-being only in the group that found the Beirut explosion more stressful.psychological well-being. Conclusion Self-efficacy is important for reducing people’s depression and improving their psychological well-being during the Lebanon crises and also mediates the influence of anxiety in response to the viral epidemic on their psychological well-being in some people. Key words: COVID-19, Explosion, psychological, anxiety